Serum periostin levels in early in pregnancy are significantly altered in women with miscarriage - A. Freis; J. Schlegel; R. J. Kuon; A. Doster; J. Jauckus; T. Strowitzki; A. Germeyer (BMC, 2017)
Abstract Background Miscarriage is a common complication in pregnancy and there is still a lack of biomarkers usable in asymptomatic patients before the event occurs. Periostin (PER), whose levels rise particularly during injury or inflammation, has been shown to play an important local role in implantation and early embryonic development. As PER has been described as a biomarker in various medical conditions we intended to evaluate if changes in PER serum levels may help to identify women at risk for spontaneous abortion in the first trimester. Methods Women between 18 and 42 years without confounding comorbidities who conceived by IVF/ICSI and ovarian hyperstimulation were analysed in the study after informed consent. Maternal serum samples from 41 patients were assessed at the time of pregnancy testing (PT) and the following first ultrasound checkup (US). Patients were subsequently divided in two groups: (1) patients with subsequent miscarriage in the first trimester (n = 18) and (2) patients with ongoing pregnancy (n = 23), allowing for statistical analysis and investigating the change of PER levels per individual. PER levels were measured using enzyme-linked immunosorbent assay. Statistical analysis was performed using the Fisher exact and Student's t test. p ≤ 0.05 was considered to be significant. Results There was no significant difference concerning possible confounders between the two groups. We did not find any significant difference in PER levels at the time point of PT or US. By investigating the interindividual changes of PER between the two time points however, we observed that patients with a following miscarriage showed increasing levels of PER at the time point of PT compared to US in contrast to patients with an ongoing pregnancy who demonstrated a decrease in PER levels. These alterations were significant in the absolute as well as in the relative comparison. Conclusion The relative expression of PER between PT and US is significantly altered in asymptomatic women with subsequent miscarriage compared to women with ongoing pregnancy. Therefore systemic PER levels might represent a potential promising biomarker for the assessment of pregnancy outcome. Trial registration Not applicable.